Experiential Education - an Opportunity for Compensatory Education - Zoglowek, Herbert; Kuhl, Hermann (Revija za elementarno izobraževanje, 2022)
The article describes a project about ‘experiential education’ at a school in Germany. The main educational objective is to offer an alternative way of teaching pupils who show destructive and aggressive behaviour. After a critical analysis of the concept of experiential education with regard to its educational relevance, the conceptual design and implementation of the project is presented. The experiences gained through participant observation and interviews can be interpreted in such a way that pupils with behavioural problems can gain a new, different access to themselves through special movement- and social-related activities, an outcome which has positive effects on social behaviour in the class and school climate in general and working behaviour in subject lessons specifically.